Theory and Practice of Sociosensitive and Socioactive Systems - Bellon, Jacqueline; Eyssel, Friederike; Gransche, Bruno; Nähr-Wagener, Sebastian; Wullenkord, Ricarda (Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2022)
Interactive adaptive systems increasingly become part of our everyday life. Which factors could shape this development and under which conditions will interactions with technical systems be deemed socially appropriate? The "FActors of Social Appropriateness" (FASA) Model presented in this Open Access-book provides a structured approach to our understanding of social appropriateness in human-technology interaction. The FASA Model serves to inform design choices for sociosensitive and socioactive artificial assistants. The Authors Jacqueline Bellon M.A., Research Associate at the University of Tübingen, International Center of Ethics in the Sciences and Humanities. Prof. Dr. Friederike Eyssel, Professor of Applied Social Psychology and Gender Research in the Department of Psychology and at the Center for Cognitive Interaction Technology (CITEC) at Bielefeld University. Dr. Bruno Gransche, Research Associate and Principal Investigator (PI) at the Karlsruhe Institute of Technology (KIT), Institute of Technology Futures. Sebastian Nähr-Wagener M.A., Research Associate at the Karlsruhe Institute of Technology (KIT), Institute of Technology Futures. Dr. Ricarda Wullenkord, Research Associate at the Center for Cognitive Interaction Technology (CITEC) at Bielefeld University.